Food Security Climate, Agriculture and Socio-Economics (CASE) Maps - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
Food Security CASE Maps is an interactive visualization tool, developed in partnership with StatPlanet, to provide detailed information about a diversity of indicators, including subnational crop area and yields, national average calorie availability, and international trade flows. For more information, visit the Food Security CASE Maps blog at http://casemaps.ifpri.info